The Impact of Carboxytherapy and Treatments Combining Carboxytherapy and Selected Chemical Peels on Vascular and Pigmentary Components of the Dark Circles - Kołodziejczak A; Rotsztejn H (Clinical, Cosmetic and Investigational Dermatology, 2024)
Anna Kołodziejczak, Helena Rotsztejn Department of Cosmetology and Aesthetic Dermatology, Medical University of Lódź, Łódź, PolandCorrespondence: Anna Kołodziejczak, Email anna.kolodziejczak@umed.lodz.plObjective: Particular attention is given to the enhancement of melanin-related pigmentation (dark circles, photoaging) and vascular circles, which are commonly located in the tear trough. The objective of the study is to provide an objective evaluation of the impact of carboxytherapy and the treatment regimen combining carboxytherapy with lactobionic acid (20%, pH 2.1) or ferulic acid (14%, pH 4.0– 5.0) and ascorbic acid (12%) on skin defects in the eye area.Materials and Methods: A group of 39 Caucasian people were subjected to a series of five carboxytherapy treatments (right eye area) and five treatments combining carboxytherapy with a selected chemical peel for the skin around the eyes (left eye area). The efficacy of therapy was assessed based on parameters (MI and EI) measured with the Mexameter probe. Measurements were made in the tear trough and the middle of the lower eyelid.Results: We demonstrated that a series of carboxytherapy (right side) significantly statistically influenced the EI parameter (in different measurement points: P < 0.0001, P = 0.015, P = 0.002), which reflects the intensity of vascular circles under the eyes. Improvement of this parameter by 7.2 units was also shown in the tear trough in 82.1% of participants after the application of carboxytherapy combined with acids (left side) on the valley of tears for this parameter (EI). Lactobionic acid and carboxytherapy were associated with a statistically significant improvement (P = 0.011) in the tear trough. In this study, a reduction in the combined pigmentation (MI plus EI) for both the right and left sides (p = 0.001 and p = 0.015, respectively) was observed.Conclusion: The study provides objective evidence for the effectiveness of sole carboxytherapy and carboxytherapy combined with acids in the reduction of dark circles, in particular vascular circles in the tear trough. Lactobionic acid, ferulic acid, and ascorbic acid can be used as safe supplements to enhance carboxytherapy.Keywords: carboxytherapy, dark circles, lactobionic acid, ferulic acid, ascorbic acid